Successful Neoadjuvant Chemotherapy for Small-Cell Neuroendocrine Carcinoma of the Pancreas: A Case Report - Li, Keyu; Yuan, Jialong; Li, Yichen; Zhang, Hao; Liu, Xubao; Ke, Nengwen (Frontiers in Oncology, 2021)
Neoadjuvant therapy for pancreatic neuroendocrine tumors may potentially aid downstaging, increase the possibility of radical surgery. We herein report a case of a 63-year-old man who had been diagnosed with locally advanced small-cell neuroendocrine carcinomas of the pancreas according to the diagnostic biopsy. The patient received 6 courses of etoposide and cisplatin as neoadjuvant therapy in an attempt to stop tumor progression, which promoted obvious tumor shrinkage without adverse effects and allowed subsequent Appleby procedure, the distal pancreatectomy with celiac artery resection. The patient showed no recurrence in the follow-up of a contrast-enhanced computed tomographic scan, which is 8 months after surgery. To the best of our knowledge, this is a rare case to report etoposide and cisplatin administration before surgery for unresectable pancreatic neuroendocrine carcinoma promoted a pathological partial response and finally achieved a radical surgery, providing a novel therapeutic option for patients with locally advanced pancreatic neuroendocrine carcinoma.